2015
DOI: 10.1007/s10067-015-3139-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of rapidly progressive-interstitial lung disease in patients with clinically amyopathic dermatomyositis

Abstract: Clinically amyopathic dermatomyositis (CADM) is a unique subset of dermatomyositis, showing a high incidence of lung involvements. The aim of this study is to identify risk factors, other than melanoma differentiation-associated protein (MDA)-5, for developing rapidly progressive-interstitial lung disease (RP-ILD) in patients with CADM. Forty CADM patients, in whom 11 patients developed RP-ILD, were enrolled. Clinical features and laboratory findings were compared between the patients with and without RP-ILD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 15 publications
8
44
1
1
Order By: Relevance
“…Elevated ESR and ferritin levels have both been associated with a poor prognosis in ILD, while high ferritin levels have been associated with a worse outcome in IIM patients . These results suggest that baseline elevation of ESR or CRP in IIM may predict a worse outcome, and should prompt frequent monitoring for disease control and eventually early treatment with immunosuppressive drugs in these cases .…”
Section: Discussionmentioning
confidence: 86%
“…Elevated ESR and ferritin levels have both been associated with a poor prognosis in ILD, while high ferritin levels have been associated with a worse outcome in IIM patients . These results suggest that baseline elevation of ESR or CRP in IIM may predict a worse outcome, and should prompt frequent monitoring for disease control and eventually early treatment with immunosuppressive drugs in these cases .…”
Section: Discussionmentioning
confidence: 86%
“…The search procedure is shown in Figure 1. Finally, 20 studies [6][7][8]10,11,13,14,[16][17][18][19][20][21][22][23][24][25][26][27][28] comprising 1500 patients with CDM or CADM met the selection criteria and were included in the study. From these 20 studies, 26 demographic, clinical and laboratory characteristics were analyzed.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Cutaneous ulceration commonly occurs on Gottron's papules, the elbows and knees, and in periungual areas [2,9,11]. Recent studies have shown that presence of anti-MDA5 antibodies and cutaneous ulceration are strong risk factors for RP-ILD [12,13]. Palmar papules are usually painful and commonly occur on the metacarpophalangeal and interphalangeal joint creases of the palms [9].…”
Section: Discussionmentioning
confidence: 99%